2004
DOI: 10.1002/ajim.10350
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of hydroxyproline in blood: A biological marker in occupational exposure to asbestos and its relationship with Pi*Z and Pi*S polymorphism in the alpha‐1 antitrypsin gene

Abstract: Blood OHP concentration could be used for monitoring human exposure to asbestos, either as a marker for occupational monitoring or as an additional clinical parameter in diagnostic exploration of asbestosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(35 reference statements)
1
2
0
Order By: Relevance
“…In this study, HC’s absorption peaked at 140 min. Consistent with our observations, orally ingested collagen was proven to undergo degradation into oligopeptides that can be detected in blood two hours after ingestion [ 43 ], and hydroxyproline blood concentration was demonstrated to range in µM (nmol/mL) [ 44 , 45 ]. Interestingly, Taga et al reported that following the ingestion of 25 g of fish gelatin hydrolysate, the plasma concentrations reached about 100 nmol/mL for “total hydroxyproline-containing peptides” between 1 and 2 h and returned to the initial level after 6 h [ 46 ].…”
Section: Discussionsupporting
confidence: 84%
“…In this study, HC’s absorption peaked at 140 min. Consistent with our observations, orally ingested collagen was proven to undergo degradation into oligopeptides that can be detected in blood two hours after ingestion [ 43 ], and hydroxyproline blood concentration was demonstrated to range in µM (nmol/mL) [ 44 , 45 ]. Interestingly, Taga et al reported that following the ingestion of 25 g of fish gelatin hydrolysate, the plasma concentrations reached about 100 nmol/mL for “total hydroxyproline-containing peptides” between 1 and 2 h and returned to the initial level after 6 h [ 46 ].…”
Section: Discussionsupporting
confidence: 84%
“…In this context the levels of t-Hyp found in blood of previously asbestos-exposed workers, suffering from asbestosis, were elevated in comparison to the levels of t-Hyp found in blood of non-exposed controls and even dose-response relations were reported [23]. As the lung is the target organ for asbestos and asbestos-related diseases, it may be hypothesized that inflammation processes involved in asbestosis might lead to decomposition of collagen in lung tissue.…”
Section: Introductionmentioning
confidence: 88%
“…The exposure assessments of each substance are based on measurements and/or data present in the literature, studied and evaluated by special groups of occupational medicine experts. There are different JEM, created and available from various organizations of different countries, their use is very common for the identification of exposed and unexposed personnel, in order to execute epidemiological studies, which are an instrument ready to use, providing an initial estimation of the correlation between the profession and exposure to each specific substance, in the absence of data on concentration measures (environmental sampling and / or personal) (6,8,21,(34)(35)(36)(37). It should be noted that JEM take into account only marginally other risk factors such as materials and equipment used while performing the work.…”
Section: Original Articlementioning
confidence: 99%